The Meaning Of Life For Athletes With Disabilities - Ayerzi Oktal; Amin Akbar (STAMINA, 2026)
Athletes with disabilities often face challenges in accepting their condition, losing their direction, and finding meaning in life after experiencing a disability. Although various studies have identified factors related to meaningfulness in life among people with disabilities, research on how athletes with disabilities construct meaning in life through their experiences in Paralympic sport remains limited. Therefore, this study aims to explore the meaningfulness of athletes with disabilities through their experiences in Paralympic sport. This study employed a qualitative, phenomenological design and was analyzed using Interpretative Phenomenological Analysis (IPA). Participants were selected using purposive sampling and consisted of three athletes with disabilities: a blind chess athlete, a physically disabled table tennis athlete, and a physically disabled bowling athlete. All participants had been active athletes for at least 1 year and had experience competing in national-level competitions. Data were collected through semi-structured interviews, observation, and document analysis. Findings indicate that participation in Paralympic sport helps participants move from a state of existential emptiness to self-acceptance, increased self-confidence, and personal development. Social support from family, coaches, and fellow athletes reinforces this process, resulting in positive changes in psychological, social, educational, and economic aspects that ultimately shape a sense of meaning in life. The themes of process and self-development emerged as central themes connecting the entire process of developing meaningfulness in athletes with disabilities